2022
DOI: 10.3390/ijms232213664
|View full text |Cite
|
Sign up to set email alerts
|

Episignature Mapping of TRIP12 Provides Functional Insight into Clark–Baraitser Syndrome

Abstract: Clark–Baraitser syndrome is a rare autosomal dominant intellectual disability syndrome caused by pathogenic variants in the TRIP12 (Thyroid Hormone Receptor Interactor 12) gene. TRIP12 encodes an E3 ligase in the ubiquitin pathway. The ubiquitin pathway includes activating E1, conjugating E2 and ligating E3 enzymes which regulate the breakdown and sorting of proteins. This enzymatic pathway is crucial for physiological processes. A significant proportion of TRIP12 variants are currently classified as variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Given the inhibitory effect on MDC1 foci formation, it is likely that the IDR of TRIP12 simultaneously participates in the chemosensitivity of cancer cells. Finally, numerous studies have reported an association between Trip12 mutations and intellectual deficiencies such as Clark-Baraister syndrome 21,54 . The molecular mechanisms involved are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the inhibitory effect on MDC1 foci formation, it is likely that the IDR of TRIP12 simultaneously participates in the chemosensitivity of cancer cells. Finally, numerous studies have reported an association between Trip12 mutations and intellectual deficiencies such as Clark-Baraister syndrome 21,54 . The molecular mechanisms involved are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…TRIP12 alterations have been involved in several pathologies. Indeed, TRIP12 gene mutations are tightly associated with intellectual disabilities such as Clark-Baraitser syndrome 20,21 and autism spectrum disorders 2224 . It is also reported that TRIP12 protein is overexpressed in several types of cancer and preneoplastic lesions 3,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously published articles were used as a basis for functional annotation and episignature cohort comparison [ 22 24 ]. We assessed the percentage of differentially methylated probes (DMPs) shared between the MOWS episignature and those referring to 56 neurodevelopmental disorder episignatures included in the EpiSign v3 clinical classifier, and produced heatmaps and circos plots.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the EpiSign classifier has proven to be a useful tool for the reclassification of VUS as well as to confirm/reject a clinical diagnosis [ 21 ]. EpiSign v3 assay has been reported to detect over 58 episignatures across more than 65 diseases, in particular NDDs [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%